PKCβII specifically regulates KCNQ1/KCNE1 channel membrane localization. (January 2020) - Braun, Chen; Parks, Xiaorong Xu; Qudsi, Haani; Lopes, Coeli M.
Abstract: The slow voltage-gated potassium channel (IKs) is composed of the KCNQ1 and KCNE1 subunits and is one of the major repolarizing currents in the heart. Activation of protein kinase C (PKC) has been linked to cardiac arrhythmias. Although PKC has been shown to be a regulator of a number of cardiac channels, including IKs, little is known about regulation of the channel by specific isoforms of PKC. Here we studied the role of different PKC isoforms on IKs channel membrane localization and function. Our studies focused on PKC isoforms that translocate to the plasma membrane in response to Gq-coupled receptor (GqPCR) stimulation: PKCα, PKCβI, PKCβII and PKCε. Prolonged stimulation of GqPCRs has been shown to decrease IKs membrane expression, but the specific role of each PKC isoform is unclear. Here we show that stimulation of calcium-dependent isoforms of PKC (cPKC) but not PKCε mimic receptor activation. In addition, we show that general PKCβ (LY-333531) and PKCβII inhibitors but not PKCα or PKCβI inhibitors blocked the effect of cPKC on the KCNQ1/KCNE1 channel. PKCβ inhibitors also blocked GqPCR-mediated decrease in channel membrane expression in cardiomyocytes. Direct activation of PKCβII using constitutively active PKCβII construct mimicked agonist-induced decrease in membrane expression and channel function, while dominant negative PKCβII showed no effect. This suggests that the KCNQ1/KCNE1 channel was not regulated by basal levels of PKCβII activity. Our results indicate that PKCβII is a specific regulator of IKs membrane localization. PKCβII expression and activation are strongly increased in many disease states, including heart disease and diabetes. Thus, our results suggest that PKCβII inhibition may protect against acquired QT prolongation associated with heart disease. Highlights: Our studies focused on IKs channel regulation by prolonged activation of specific PKC isoforms. We showed PKCβII activation inhibited IKs membrane localization and function in heterologous systems and cardiomyocytes. We showed PKC regulation of channel membrane localization is specific to PKCβII. PKCβII has been previously shown to be chronically activated in heart disease. Inhibition of PKCβII may prevent remodeling that is expected to lead to QTc prolongation and cardiac arrhythmias.